2015
DOI: 10.1590/0103-5150.028.002.ao15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of static balance of elderly women through two methods: computerized photogrammetry and accelerometer

Abstract: Introduction The aging process produces functional and structural deficits in the body, among these changes we highlight the changes in balance. Objective This study aims to compare the computed photogrammetry and accelerometer to assess static balance in the elderly. Methods This was an observational, cross-sectional study. The study included 112 female subjects participating in a mothers club, where the balance assessment was performed using computerized photogrammetry and accelerometer. Results Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…When evaluating the orthostatic posture, notable differences were observed in the measurements: vertical alignment of the right trunk, vertical alignment of the right and left body, angle of the left ankle and asymmetry in the frontal plane. These results agree with those found by Nunes, Fonseca and Scheicher 29 , who reported that the elderly who do not practice physical exercise are more likely to anteriorization and lateralization of the center of gravity. On the other hand, in the studies by Valduga et al 30 , there were no significant differences in posture between the elderly who practice and do not practice activities.…”
Section: Discussionsupporting
confidence: 93%
“…When evaluating the orthostatic posture, notable differences were observed in the measurements: vertical alignment of the right trunk, vertical alignment of the right and left body, angle of the left ankle and asymmetry in the frontal plane. These results agree with those found by Nunes, Fonseca and Scheicher 29 , who reported that the elderly who do not practice physical exercise are more likely to anteriorization and lateralization of the center of gravity. On the other hand, in the studies by Valduga et al 30 , there were no significant differences in posture between the elderly who practice and do not practice activities.…”
Section: Discussionsupporting
confidence: 93%
“…Accelerometry allows the analysis of specific aspects related to this factor and it has been proposed as a new implementation method due to the inexpensiveness, reliability, portability and comfortability for the evaluator [9,10]. Numerous studies with accelerometers have evaluated balance and have been focussed on adult or elderly populations, especially in cases of risk of falling [11][12][13]. Balance accelerometric evaluation has been compared repeatedly with clinical trials and tests results, having positive results in different populations such as: (a) elderly people with a history of falls or a cerebrovascular accident, (b) children with dyslexia, (c) patients with Huntington's and Parkinson's disease and (d) patients with progressive cerebellar ataxia, and with vestibular disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Por conta ainda de sua importância clínica, Portney et al [5] destacaram que a avaliação postural do indivíduo deve ser incluída no processo avaliativo. Existem diversos métodos de análise postural, Oliveira et al [6] e Camelo et al [7] descreveram a fotogrametria computadorizada como uma das principais ferramentas atuais, sendo utilizada como auxílio durante o exame físico para quantificar alterações posturais e alterações no equilíbrio estático, além de ser um instrumento básico para prática clínica e como instrumento de pesquisa.…”
Section: Introductionunclassified
“…Integrante do Centro Acadêmico de Fisioterapia da UFS/Lagarto, ocupando o cargo na secretaria. 4 Biólogo com Ênfase em Genética pela Universidade Estadual do Sudoeste da Bahia (UESB), Mestre em Recursos Genéticos Vegetais pela Universidade Federal do Recôncavo da Bahia (URFB), Doutor em Genética e Biologia Molecular pela Universidade Estadual de Santa Cruz (UESC) e Técnico em Biologia na Universidade Federal de Sergipe (UFS) 5 Graduada em Fisioterapia da Universidade Federal de Sergipe, Campus Lagarto 6 Graduanda do 5º Ciclo do curso de Fisioterapia da Universidade Federal de Sergipe, Campus Professor Antônio Garcia Filho -Lagarto/SE; Monitora do módulo de Habilidades e Atitudes em Fisioterapia I (2018 e 2019). Membro Fundadora da Liga Acadêmica de Terapias Manuais e Alternativas (LATMA), exercendo atualmente o cargo de diretora de extensão (2018/2019/2020).…”
unclassified